Efficacy of crizotinib in ALK fusion variants - Kobayashi, Tetsu; Fujimoto, Hajime; Gabazza, Esteban C. (Journal of Thoracic Disease, 2016)
In 1995, rearrangement of the anaplastic lymphoma kinase (ALK) gene was first reported as a fusion gene in anaplastic large cell non-Hodgkin lymphoma, and in 2005 it was again on focus when Mano et al. reported that echinoderm microtubule-associated protein-like4 (EML4)-ALK fusion gene is a powerful oncogene in lung cancer (1,2).